The association of self-reported respiratory system diseases with farming activity among farmers of greenhouse vegetables. Issue 7 (July 2019) - Li, Jiangping; Li, Yanxia; Tian, Danian; Yang, Huifang; Dong, Lijun; Zhu, Lingqin
Objectives: Several studies have investigated the link between agricultural activities of open-field farmers and the prevalence of respiratory diseases, but the relationship with greenhouse vegetable farmers remains unclear. Methods: A total of 1, 366 participants from four villages in China provided information about their agricultural activities and symptoms of diagnosed respiratory system diseases. The Poisson regression model and zero-inflated Poisson regression model were used to assess the association between diseases, symptoms, and agricultural activities. Results: The prevalence of respiratory diseases was 3.59%, and the rates of four main symptoms (cough, tachypnea, chest distress, and hemoptysis) were 17.21%, 8.56%, 10.25%, and 1.61%, respectively. Mix spray of pesticides associated with cough, tachypnea and chest distress, 1.740-, 3.385- and 2.882-fold likelihood were found than hand spray, and the significant association were detected in empty, general information, life-style information adjusted models. Conclusions: The relationship between agricultural activities and respiratory diseases is unclear. However, use of the mix spray method of pesticide application may increase the risk of cough, tachypnea, and chest distress.